HEALTH IMPACT OF TORNADOES: ARE OLDER ADULTS MORE RESILIENT?. (11th November 2018) - Cong, Z; Liang, D; Luo, J
Abstract: This study examines how multi-level factors affected the changes in health, Posttraumatic Symptoms Disorder (PTSD), and Posttraumatic Growth (PTG) as a result of violent tornadoes and age differences. A telephone survey with random digit dialing was conducted with 543 respondents approximately one year after two violent (EF4 and EF5) tornadoes in 2013. Respondents' addresses were used to associate individual information with block group-level variables recorded by the American Community Survey. Individual and Multilevel multinomial logistic, Poisson, and regular regressions showed that older adults were different than younger adults in several major ways. Older adults were more resilient to financial losses and stressful experiences than younger adults in having improved health or less declined health. Older adults were more vulnerable than younger adults to family members' declined mental health. Both older and younger adults' health was affected negatively by the percentage of older adults in the community.